METHOD OF NOISE MAPPING OF TRAFFIC FLOWS IN MODERN CITY - Шевченко, Ю.С. (Proceedings of National Aviation University (archive), 2012)
The issue of noise maps creation is studied on the example of small town Burshtyn. On the base of up-to-date existing and previously created by author mathematical models equivalent noise levels from traffic flows modeling have been carried out. To verify proposed models for calculation of noise from particular cars and from traffic flows and the effects of sound propagation from noise source to receiver experimental researches have been done. On the base of collected data empirical coefficients for each category of transport means have been defined. Horizontal noise map of Burshtyn has been created. The analysis of soundscape state ahs been done and recommendations for decreaseing of noise levels from two main roads have been proposed. Further researches aim to create not only horizontal, but also vertical noise maps for small districts, as well as their cross and longitudinal sections. Creation of such maps is up-to-date question for analysis of soundscape state on the territory of multistory buildings that is a characteristic feature of modern cities.